Turkey and Kurdistan Regional Government (KRG) Relations: A Soft Power Approach towards Kurdish Question - Al-Asyura, M Khairil Zaki; Basyar, M. Hamdan (Andalas Journal of International Studies (AJIS), 2022)
Turkey has long regarded Kurds as a homogenous entity that could threaten its territorial integrity and national security. There is ‎animosity by the Turkish government towards the Kurds. ‎This article attempts to analyze why there has been a paradigm shift and enhancement in Turkey-KRG relations, especially during AKP tenure, while analyzing the extent to which the ‎effectiveness of the Turkey-KRG relationship can help Turkey resolve its Kurdish ‎issue in peaceful ways. This research uses offensive realism as an analytical tool while deploying qualitative methods through ‎explanatory and descriptive approaches in answering the problems raised. The ‎study shows that the paradigm shift and the enhancement in Turkey-KRG relations can occur because Turkey seeks to pursue its goal, ‎being a regional hegemon. In this way, Turkey can guarantee its survival, increase ‎welfare, and preserve its political doctrine. However, the enhancement of Turkey-‎KRG relations shows less significant effectiveness in overcoming the Kurdish ‎issue. As the Kurdish question is a domestic issue, it is Turkey itself that must find ‎a solution‎ to